A Survey Of Knowledge and Clinical Consideration On Fiber Post For Restoration Of Endodontically Treated Tooth Among Undergraduate Dentistry Students - Mohamed, Nusima; Mohd Rasdi, Nurul Atiqah; Che Lah, Nur Fatin Izzati; Ismail, Nor Azlina (SciDoc Publishers, 2024)
Indexed by Scopus